Spatially Enabled Society - Dalyot, S. (International Federation of Surveyors (FIG), 2020)
Report presents some problems: spatial needs of societies; the role of land administration, land management and land governance in spatially enabled societies; key elements for a spatially enabled society, definition of the term “Spatially Enabled Society”.